2021
DOI: 10.3390/dj9090103
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dental Implant Diameter and Bone Quality on the Biomechanics of Single-Crown Restoration. A Finite Element Analysis

Abstract: Background: Success of an implant-supported prosthesis is highly dependent on implant diameter and bone quality. The objective of this study is to assess these two variables under axial or 30° angulated loading. Methods: The study was conducted using finite element model simulations of dental implants with an unchanging length of 6.5 mm and varying diameters of Ø3.3; Ø3.5; Ø3.75; Ø4, Ø4.25 and Ø4.75 mm. The implants were placed in an axial position and a 2 mm high straight transepithelial (intermediate abutmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Most studies have evaluated the maximum stress using chewing forces in normal ranges with different dental implant dimensions and prosthetic structures ( Cho et al, 2016 , Farronato et al, 2019 , Kharsan et al, 2019 , Pournasrollah et al, 2019 , Fiorillo et al, 2020 , Anitua et al, 2021 ). A previous study determined that the implant-abutment connection is a key point in long-term clinical success ( Kharsan et al, 2019 , Pournasrollah et al, 2019 ), whereas others studies reported that stress decreases as the implant diameter increases ( Cho et al, 2016 , Anitua et al, 2021 ). Another investigation developed a novel conical dental implant connection that generated lower maximum stress values both on the implant components and on the peri -implant tissues ( Fiorillo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have evaluated the maximum stress using chewing forces in normal ranges with different dental implant dimensions and prosthetic structures ( Cho et al, 2016 , Farronato et al, 2019 , Kharsan et al, 2019 , Pournasrollah et al, 2019 , Fiorillo et al, 2020 , Anitua et al, 2021 ). A previous study determined that the implant-abutment connection is a key point in long-term clinical success ( Kharsan et al, 2019 , Pournasrollah et al, 2019 ), whereas others studies reported that stress decreases as the implant diameter increases ( Cho et al, 2016 , Anitua et al, 2021 ). Another investigation developed a novel conical dental implant connection that generated lower maximum stress values both on the implant components and on the peri -implant tissues ( Fiorillo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Implants and natural teeth respond differently to masticatory forces and these differences are related to the existence or absence of periodontal ligaments, which serve as an elastic buffer. Analyzing the biomechanical responses of these structures is challenging because of the complexity of biomaterials, dental anatomy, and microstructural details (Anitua et al 2021a and2021b). The FEA, which standardizes the parameters, is a suitable and analytic method of evaluating biomechanical behaviors in complex geometries.…”
Section: Discussionmentioning
confidence: 99%
“…The use of transepithelial abutments in all the implants probably contributed to achieve a low number of technical complications in both groups and helped to dissipate implant loads thus positively influencing in the biological performance too [22,49,50]. This total homogeneity in the type of prosthetic restoration and in the type of implant surface together with a well-balanced sampling in relation to patients´ sex and age, number of smokers, bone type, insertion torque or type of antagonist, are relevant strengths of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…As the length of the implant is reduced, it has been suggested to increase the diameter to enhance the boneimplant contact and optimize the distribution of stress in the bone, particularly in cases of low bone density. [22] Short implants are not limited to cases of limited available bone. Currently, short implants can be preferred to maintain as much pristine bone as possible, even when standard implants could be housed.…”
Section: Introductionmentioning
confidence: 99%